Clinical Manifestations of Iatrogenic Magnetism in Subjects After Receiving COVID-19 Injectables: Case Report Series - Tuuminen, Tamara; Suominen, Pasi J; Ahonen, Mikko (International Journal of Innovative Research in Medical Science, 2025)
A series of cases of COVID-19 vaccine-injected patients suffering from iatrogenic magnetism is described. The attachment of massive metallic objects (up to 70 grams) to different parts of the body is a real phenomenon that may present additional health risks if such patients are subjected to magnetic resonance imaging (MRI). The iatrogenic magnetism phenomenon typically appears several months after the injection. More likely, injected DNA plasmids, or modified mRNAs, translated into the spike protein, or into junk peptides formed through frameshifts, may engender proteins with ferromagnetic properties, or may entrap endogenous iron. Importantly, the spike protein has a distant homology to hepcidin, the key regulator of iron metabolism. Redistribution of iron into the brain or other body parts may be causing iatrogenic magnetism. Pfizer vaccine lots starting with the letter “F” may be involved, although we cannot exclude the possibility that Moderna or other manufacturers’ injections may also cause this phenomenon. In our observation, the magnetism may resolve spontaneously or when nicotinamide adenine dinucleotide (NAD+) is applied. Our pilot observation needs to be corroborated in a larger cohort study.